Hazardous alcohol use is associated with greater pain interference and prescription opioid misuse among persons living with HIV and chronic pain - Belle Ngo; Jane M. Liebschutz; Debbie M. Cheng; Jonathan A. Colasanti; Jessica S. Merlin; Wendy S. Armstrong; Leah S. Forman; Marlene C. Lira; Jeffrey H. Samet; Carlos del Rio; Judith I. Tsui (BMC, 2021)
Abstract Background Alcohol use is common among persons living with HIV (PLWH), who often experience chronic pain, yet its impact on pain and opioid misuse is not fully characterized. Methods We assessed associations between hazardous alcohol use and pain interference, defined as the self-reported impact of pain on daily living, pain severity, and risk for opioid misuse among PLWH who were on long-term opioid therapy (LTOT). A cohort was recruited as part of the "Targeting Effective Analgesia in Clinics for HIV" (TEACH) study, a randomized controlled trial to improve LTOT in HIV clinics. The Alcohol Use Disorders Test (AUDIT), Brief Pain Inventory (BPI) and the Current Opioid Misuse Measure (COMM) were administered at both baseline and 12-months. Linear mixed and generalized estimating equation models, incorporating data from both time points, evaluated associations between hazardous alcohol use (AUDIT ≥8) and: pain interference (0-10), pain severity (0-10), and opioid misuse risk (COMM ≥13), adjusting for age, gender, depressive symptoms, use of non-alcohol substances, time-point, and study-arm. Results The sample was comprised of 166 participants, of which 31 (19%) reported hazardous alcohol use. The majority were male (65%), black (72%), and the mean age was 54 (range: 29-77). Hazardous alcohol use was significantly associated with higher pain interference (adjusted mean difference [AMD]: 1.02; 95% CI: 0.08, 1.96) and higher odds of opioid misuse risk (AOR: 3.73, 95% CI: 1.88-7.39), but not pain severity (AMD: 0.47, 95% CI: − 0.35, 1.29). Conclusions Hazardous alcohol use was associated with greater functional impairment in daily living from their pain and higher odds for prescription opioid misuse in this study of PLWH on LTOT. Providers should be attentive to alcohol use among PLWH who are prescribed opioids given associations with pain and opioid misuse. Trial registration ClinicalTrials.gov NCT02564341 (Intervention, September 30, 2015) and NCT02525731 (Patient Cohort, August 17, 2015). Both prospectively registered.